Exploring university-industry cooperation : Meta analysis - Jančaříková, Ester (2025)
This thesis examines university–industry cooperation (UIC) using bibli-ometric and meta-analytic approaches. It reviews over 27,000 publica-tions to trace the field's evolution and synthesises findings from 122 empirical studies to evaluate key influencing factors. The results indi-cate that human capital, governance structures, and firm capabilities have a significant impact on UIC outcomes, while traditional metrics, such as patent counts, show weaker associations. The study highlights the importance of outcome-based evaluations and provides evidence on UIC's role in driving innovation.